A cryptographic encryption technique byte – Spiral rotation encryption algorithm. (3rd April 2019) - Sanal Kumar, S.; Anfino Sherfin, S.
Abstract: Security is one of the most important fundamental issues for the communication of data in the wireless world. There are various types of encryption algorithms using different techniques like AES, DES, Triple DES, RSA, Blowfish etc. Moreover, the main aim of the encryption is to increase the level of security and minimize the time and complexity. In our research paper, we have provided a cryptographic encryption technique that encrypts the messages by using a new technique called Spiral Rotation Encryption Algorithm. The process of the algorithm is to change the data into a parallel sequence of matrices containing converted and shuffled numeric, by the process of spiral rotation about the diagonal entries so that the process of the encryption time is reduced and encryption steps are minimized.